La importancia de los juegos teatrales en los procesos de desarrollo socioafectivo en la primera infancia. (2023)
The socio-affective development of children is crucial for the rest of their lives, an aspect that must be worked on based on encouragement from their parents, for the most part. On the other hand, theater is one of the artistic manifestations, where it is considered a place of meeting and communication, of expression of ideas and emotions. However, this concept of theater is different for the children's audience, with the difference that with children in this case, early childhood will not be shown dramatic actions but rather a space through play where they can explore themselves and learn together with their parents/caregivers to understand the world around them.